Formation of Inclusive Attitudes in Students Through the Mindful Learning Approach to Islamic Religious Education - Rona Sifaun Nada; Purnomo Purnomo (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Efforts to shape students' inclusive attitudes tend to focus on structural approaches, such as multicultural integration and religious moderation policies. However, this study shows that Islamic Religious Education (IRE) learning approaches also play a role in shaping these attitudes. This study aims to analyze the application of Mindful Learning in Islamic Religious Education (IRE) learning, explain the process of developing students' inclusive attitudes, and describe its application in social interactions at SMP Negeri 10 Salatiga. This study used a qualitative approach with a case study and a single case embedded Yin design. Data were obtained through observation, interviews, and documentation involving Islamic Religious Education (IRE) teachers, Muslim students, and non-Muslim students. Data were analyzed using pattern matching, explanation building, and rival explanation examination techniques. The results show that Mindful Learning is implemented through adjustments to teaching modules, mauidhoh hasanah, personal approaches, uswah hasanah, perspective-taking activities, and dialogue spaces. This process shapes inclusive attitudes through Islamic Religious Education (IRE) learning, school policies, and students' daily interactions, which are evident in tolerance, mutual assistance, cooperation, and the ability to resolve conflicts independently. The novelty of this study lies in the role of Mindful Learning in teachers' responses to students' needs, the internalization of students' values, and the role of students as active actors in building an inclusive environment. Thus, Islamic Education learning that encourages awareness and reflection is one way to foster an inclusive attitude